Marketing communications : objectives, strategy, tactics - Rossiter, John R.; Percy, Larry; Bergkvist, Lars (London Sage publ., 2018)
Uniting industry experience with academic expertise, the authors combine marketing communications and advertising with the branding perspective to provide students with a practical planning system and a seven-step approach enabling them to create a consistent and comprehensive marketing plan.
Includes bibliographical references and indexes.
Keywords: Communication in marketing; Positioning (Advertising); Marketing; Communication of information; Business